Anxiety symptoms and quality of interaction among oncology nurses: a correlational, cross-sectional study - Karanikola,Maria NK. (2016)
Abstract OBJECTIVE To explore the severity of Anxiety Symptoms (AS) among Greek oncology nursing personnel, the degree of satisfaction from professional relationships, and potential association between them. METHOD A descriptive cross-sectional correlational study was performed in 2 Greek Oncology Hospitals, in 72 members of nursing personnel. Hamilton Anxiety Scale was used for the assessment of AS severity and the Index of Work Satisfaction subscale "Satisfaction from Interaction" for the degree of satisfaction from professional relationships among nursing personnel (NN) and between nursing personnel and physicians (NP). RESULTS 11% of the sample reported clinical AS [≥26, scale range (SR): 0-52]. Satisfaction from NN [5.10 (SD: 1.04), SR: 1-7], and NP [4.21 (SD: 0.77), SR: 1-7] professional interaction were both moderate. Statistically significantly associations were observed between clinical AS and satisfaction from NN (p=0.014) and NP (p=0.013) professional interaction. CONCLUSIONS Anxiety reduction interventions and improvement of professional relationships are essentials in order to reduce oncology nurses' psychological distress.